Training Graduate Students' Shaping Skills in an Immersive Virtual Reality Environment - Gifty Owusu; Nicole Luke (MDPI AG, 2024)
Graduate students need a wide range of professional skills, and shaping is one of the critical skills they must learn. This study trained graduate students to acquire shaping skills in an immersive virtual reality environment using the Portable Operant Research Teaching Lab (PORTL). To date, no known study has (a) evaluated the effectiveness of shaping skills training for graduate students or (b) attempted to teach these skills in a virtual environment. We used a single-case A-B design across participants with three graduate students who learned shaping skills in an immersive virtual reality environment using the PORTL curriculum. The shaping skills comprised creating a teaching plan, setting up for a session, delivering reinforcement, and evaluating a session. For all participants, training resulted in improvement in shaping skills. Participants also maintained the shaping skills for a minimum of two weeks. Further, the effect of the training generalized to a novel confederate learner for all participants. Additionally, participants showed high satisfaction with learning shaping skills in an immersive virtual reality (iVR) environment.